2015
DOI: 10.1039/c4ob01810a
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel fluorescence probe capable of assessing the cytoplasmic entry of siderophore-based conjugates

Abstract: A novel fluorescence probe capable of assessing the cytoplasmic entry of siderophore-based conjugates was synthesized and evaluated by photochemical characterization and cell-based assays. The specific responsiveness to the cytoplasmic entry of the probe was implemented by adopting a disulfide linker, whose cleavage under the reducing conditions of the cytoplasm induced the display of a distinctive fluorescence signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Conjugates of DFOB and the DNA intercalators nalidixic acid ( 34 ) or anthraquinone carboxylic acid ( 35 ) were prepared to examine the potential to induce Fenton-based damage to DNA upon the localization of the Fe­(III)–DFOB intercalator to DNA . A fluorescent moiety appended to DFOB with a linking region containing a cleavable disulfide bond has been prepared ( 36 ) to measure cytoplasmic transport and processing of FOB in vitro and as a xenosiderophore in E. coli …”
Section: Semi-synthesis Of Dfobmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjugates of DFOB and the DNA intercalators nalidixic acid ( 34 ) or anthraquinone carboxylic acid ( 35 ) were prepared to examine the potential to induce Fenton-based damage to DNA upon the localization of the Fe­(III)–DFOB intercalator to DNA . A fluorescent moiety appended to DFOB with a linking region containing a cleavable disulfide bond has been prepared ( 36 ) to measure cytoplasmic transport and processing of FOB in vitro and as a xenosiderophore in E. coli …”
Section: Semi-synthesis Of Dfobmentioning
confidence: 99%
“…116 A fluorescent moiety appended to DFOB with a linking region containing a cleavable disulfide bond has been prepared (36) to measure cytoplasmic transport and processing of FOB in vitro and as a xenosiderophore in E. coli. 117 Antibiotic Adducts (37−43). A small suite of siderophore−antibiotic conjugates, classified as sideromycins, exist in nature, including the albomycins, salmycins, microcins, and ferrimycin A1.…”
Section: ■ Semi-synthesis Of Dfobmentioning
confidence: 99%
“…This peptide delivered the aminoglycoside into mammalian cells, affording clearance of intracellular pathogenic bacteria after cleavage of the disulfide linker and release of both antibiotics. Recently, the self-immolative disulfide linker was employed for a siderophore–fluorophore conjugate and shown to provide intracellular release of the fluorophore in a Gram-negative strain [55]. Herein, we report that the disulfide-linked conjugate Ent–SS–Cipro 2 exhibits antibacterial activity against E. coli independent of intracellular siderophore hydrolysis, which contrasts the requirements for the activity of the structurally similar alkyl-linked conjugate Ent–Cipro 1 (Scheme 1).…”
Section: Introductionmentioning
confidence: 89%
“…1-3a). For example, it was demonstrated that the fluorophore 4-amino-1,8-naphthalimide can be attached to desferrioxamine B with a disulfide-containing linker that dissociates once the conjugate enters the cytoplasm and results in release of the fluorophore [71]. To be more flexible regarding the chemical nature of the cargo molecules, linker design in principle offers the potential to release cargo molecules by cellular esterases, phosphatases or reductases [72,73].…”
Section: Illicit Transport Using Siderophore Conjugatesmentioning
confidence: 99%